I-2-catalyzed regioselective Oxo- and hydroxy-acyloxylation of alkenes and enol ethers: a facile access to alpha-acyloxyketones, esters, and diol derivatives - Reddi, Rambabu N.; Prasad, Pragati K.; Sudalai, Arumugam (Organic Letters, 2014)
I-2-catalyzed oxo-acyloxylation of alkenes and enol ethers with carboxylic acids providing for the high yield synthesis of a-acyloxyketones and esters is described. This unprecedented regioselective oxidative process employs TBHP and Et3N in stoichiometric amounts under metal-free conditions in DMSO as solvent. Additionally, I-2-catalysis allows the direct hydroxy-acyloxylation of alkenes with the sequential addition of BH3 center dot SMe2 leading to monoprotected diol derivatives in excellent yields.